Progress in Wall Turbulence 2 Understanding and Modelling - Stanislas, Michel; Jimenez, Javier; Marusic, Ivan (ERCOFTAC Series,, 2016)
This is the proceedings of the ERCOFTAC Workshop on Progress in Wall Turbulence: Understanding and Modelling, that was held in Lille, France from June 18 to 20, 2014. The workshop brought together world specialists of near wall turbulence and stimulated exchanges between them around up-to-date theories, experiments, simulations and numerical models. This book contains a coherent collection of recent results on near wall turbulence including theory, new experiments, DNS, and modeling with RANS, LES.The fact that both physical understanding and modeling by different approaches are addressed by the best specialists in a single workshop is original.